3D‐Positioning of Nanoparticles in High‐Curvature Block Copolymer Domains. (22nd June 2021) - Leffler, Vanessa B.; Ehlert, Sascha; Förster, Beate; Dulle, Martin; Förster, Stephan
Abstract: The defined assembly of nanoparticles in polymer matrices is an important precondition for next‐generation functional materials. Here we demonstrate that a defined three‐dimensional nanoparticle assembly within the unit cells can be realized by directly linking the nanoparticles to block copolymers. We show that for a range of nearly symmetric to unsymmetric block copolymers there are only two formed structures, a hexagonal lattice of P 6/ mmm ‐symmetry, where the nanoparticles are located in 1D‐arrays within the cylindrical domains, and a cubic lattice of Im3m‐symmetry, where the nanoparticles are located in the octahedral voids of a BCC‐lattice, corresponding to the structure of ferrite steel. We observe the block length ratio and thus the interfacial curvature to be the most important parameter determining the lattice type. This is rationalized in terms of minimal chain extension such that domain topologies with large positive curvature are highly preferred. Already volume fractions of only one percent are sufficient to destabilize a lamellar structure and favor the formation of highly curved interfaces. The study thus demonstrates how nanoparticles can be located on well‐defined positions in three‐dimensional unit cells of block copolymer nanocomposites. This opens the way to functional 3D‐nanocomposites where the nanoparticles need to be located on defined matrix positions. Abstract : By directly linking nanoparticles to block copolymers, defined three‐dimensional nanoparticle assemblies can be realized within domain unit cells. The block length ratio is the most important parameter determining the lattice type. Volume fractions of domains with large positive curvature of only one percent are already sufficient to destabilize lamellar structure and favor the formation of highly curved interfaces.